PESAN PERSUASI BEAUTY INFLUENCER PADA AKUN YOUTUBE TASYA FARASYA DALAM KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN: STUDI PENERAPAN ELABORATION LIKELIHOOD MODEL - Nadya Ananda Rezky Ichwan; Iwansyah Irwansyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2021)
Abstract Persuasion messages is messages conveyed through persuader communication skill which aim to convince or persuade the persuadee to follow what the persuader wants. This study aims to discuss the ability of beauty influencer persuasion messages in influencing beauty product purchasing decisions through Tasya Farasya’s Youtube channel. This study uses one of the persuasion models as a “blade of analysis”, namely Elaboration Likelihood Model (ELM) to determine the path to be taken by subscriber Tasya Farasya in receiving messages using the concept of motivation. The method, by developing existing hypotheses or theories. The results showed that Tasya Farasya’s ability to convey messages to her followers could make this messages as one of the references in deciding to purchase cosmetic products, because to informants were able to process messages conveyed by beauty influencers through Tasya Farasya’s youtube account with strong motivation. This is evidence by the results of research which have found that informants have involvement, differences of opinion and critical thingking in reciving persuasion messages before diciding to buy beauty products.